Analysis of the evolution of placental oxidative stress research from a bibliometric perspective - Chen, Ailing; Tian, Mengyuan; Luo, Zouqing; Cao, Xiaohui; Gu, Yanfang (Frontiers in Pharmacology, 2024)
Background: Research on placental oxidative stress is pivotal for comprehending pregnancy-related physiological changes and disease mechanisms. Despite recent advancements, a comprehensive review of current status, hotspots, and trends remains challenging. This bibliometric study systematically analyzes the evolution of placental oxidative stress research, offering a reference for future studies. Objective: To conduct a comprehensive bibliometric analysis of the literature on placental oxidative stress to identify research hotspots, trends, and key contributors, thereby providing guidance for future research. Methods: Relevant data were retrieved from the Web of Science Core Collection database and analyzed using VOSviewer, CiteSpace, and the bibliometrix package. An in-depth analysis of 4,796 publications was conducted, focusing on publication year, country/region, institution, author, journal, references, and keywords. Data collection concluded on April 29, 2024. Results: A total of 4,796 papers were retrieved from 1,173 journals, authored by 18,835 researchers from 4,257 institutions across 103 countries/regions. From 1991 to 2023, annual publications on placental oxidative stress increased from 7 to 359. The USA (1,222 publications, 64,158 citations), the University of Cambridge (125 publications, 13,562 citations), and Graham J. Burton (73 publications, 11,182 citations) were the most productive country, institution, and author, respectively. The journal Placenta had the highest number of publications (329) and citations (17,152), followed by the International Journal of Molecular Sciences (122 publications). The most frequent keywords were "oxidative stress," "expression," "pregnancy," "preeclampsia," and "lipid peroxidation." Emerging high-frequency keywords included "gestational diabetes mellitus," "health," "autophagy," "pathophysiology," "infection," "preterm birth," "stem cell," and "inflammation." Conclusions: Over the past three decades, research has concentrated on oxidative stress processes, antioxidant mechanisms, pregnancy-related diseases, and gene expression regulation. Current research frontiers involve exploring pathophysiology and mechanisms, assessing emerging risk factors and environmental impacts, advancing cell biology and stem cell research, and understanding the complex interactions of inflammation and immune regulation. These studies elucidate the mechanisms of placental oxidative stress, offering essential scientific evidence for future intervention strategies, therapeutic approaches, and public health policies.